Bowel obstruction by ingestion of superabsorbent polymer balls - Adil Mohamed; Hamid Qoura; Ibtisam Alshuili; Moanes Karim; Ahmed Abushosha; Niam Abdulsattar; Mohamed Hassan (Elsevier, 2019)
Ingestion of foreign bodies is a common complaint among children. However, few cases require surgical intervention [1] of non-food foreign bodies in young children [2].This study reports 2 cases of intestinal obstruction by superabsorbent gel balls in children ages 15 months and 18 months. Both presented with symptoms and signs of small bowel obstruction. The first patient underwent two operations during the same admission for other missing balls. Both patients did well postoperatively and were discharged home.Superabsorbent balls or polymer balls are new and emerging unexpected causes of intestinal obstruction. Their ingestion causes catastrophic sequelae; these items should always be kept out of the reach of children [3]. Keywords: Polymer balls, Water beads, Intestinal obstruction in children, Ingestion of foreign body